POLA KOMUNIKASI QUR’ANI:REFLEKSI TERHADAP KESANTUNAN KOMUNIKASI ANTARAMAHASISWA DAN DOSEN DI PERGURUAN TINGGI ISLAM - Fa’atin, Salmah (QUALITY, 2017)
This study examines the pattern of communication in the perspective of the Qur'an and implements the moral values in it within the scope of Islamic Higher Education, especially the reflection on the politeness of communication between students and lecturers. The method used is descriptive-qualitative, with the hermeneutic approach to understand the verses that contain the term communication, and analyze it with Islamic education approach to reflect it in the phenomenon of politeness of student and lecturer communication in the Islamic campus. The results show that the principles and ethics of communication in the Qur'an are in line with the theory of language politeness. The theory of linguistic politeness is used to photograph and measure the degree of politeness of student and lecturer communication. There are still language-linguistic inconsistencies to lecturers, and communication anxiety experienced by lecturers and students. Finally, both lecturers and students should re-internalize and implement ethical moral values to communicate well in accordance with the teachings of the Qur'an to realize the relationship of synergy and harmony, and prepare the generations of Qur'ani whose character is commendable.